ON THE BOUNDEDNESS PROPERTIES OF MIKHLIN OPERATOR ON GENERALIZED MORREY SPACES - Ramadana, Yusuf; Rosali, Dwi Fitriani (Program Studi Matematika, Universitas Nusa Cendana, 2023)
In this paper we investigate the boundedness of Mikhlin perators on generalized Morrey spaces. Theresults show that the operators are bounded on generalized Morrey spaces under some assumptions.